Pemberdayaan Dan Sosialisasi Usaha Mikro Melalui Digital Marketing Dan Branding Terhadap Beberapa UMKM Di Kelurahan Kepanjenkidul Kota Blitar - M. Wesla Dhifayana Sukirman; Ririt Iriani Sri S; Mohammad Wahed (Universitas Muhammadiyah Manado, 2023)
“UMKM” are one of the indicators that influence domestic economic growth. The increase in “UMKM” has a very positive impact on the domestic or national economy. In the process of increasing “UMKM”, it can be done in various ways, one of which is by providing empowerment and outreach. However, in carrying out these activities it is also required to see and study current economic aspects such as digitalization. Therefore this empowerment and socialization carries the theme of digitalization. The method used in this journal is an initial survey, data collection, analysis, and evaluation of results. From these results it can be seen that “UMKM” get input about the digitization of the economy including product marketing, business logos, product photos, social media platforms and banners.